MODEL KONSEPTUAL PEMETAAN WILAYAH POTENSIAL HILIRISASI KELAPA SAWIT BERDASARKAN DAYA SAING DAN KELEMBAGAAN PETANI SWADAYA - Safriyana, Marimin, Elisa Anggraeni, Illah Sailah (Jurnal Teknologi Industri Pertanian, 2019)
Palm oil as a leading commodity that has a role in national development, continues to experienceincreased demand, dueto it beneficial in various fields of needs. However, the problems and challenges haveprompted the government to improve its competitiveness through in-country palm oil downstream policies. Oneof the policies is smallholder farmers oil palm’s replanting to support palm oil downstream sector and toincrease the smallholder farmers’ social welfare. The crucial thing that is important to note and become thefocus of this research is the linkage of the smallholder farmers in support palm oil downstream policies,becausethe smallholder farmers as the main raw materials supplierto downstream palm oil agroindustry are stillobstructed,in relation to geographical conditions, its competitiveness, and its institutions. Therefore, a study wasneeded to produce an integrated palm oil downstream strategic planning related to the area, competitiveness,and institutional of palm oil smallholder farmers, in determining the potential area model for the development ofpalm oil downstream in order to have comparative and competitive advantages.The conceptual model of palmoil downstream’spotential areas that uses spatial analysis through geographical information system was used toobtain an overview of the palm oil condition, while competitiveness conceptual modelling uses Diamond Portercompetitivenessindex, and the institutional modelling uses Interpretative Structure Modeling (ISM) method toobtain the influential variables as the key elements in the palm oil downstream that affect the smallholderfarmers position.Keywords: competitiveness, palm oil downstream,institutional, area mapping, smallholder farmers